At the junction: two models of business responsibility for modern slavery - Mende, Janne (Human rights review, 2020)
This article develops a conceptual pattern of the reasons and scope of business responsibility for modern slavery. It introduces modern slavery as either relation or structure and designs an understanding of a broad and a narrow model of business responsibility, consisting of business power, internal and external realms of business conduct and public and private roles of companies. Crossing the two models of modern slavery with the two models of business responsibility, the article carves out the strengths and limits of their junctions. The continuous pendulum between the junctions allows to discuss how and why companies can be responsible for modern slavery. It thus contributes analytically, practically and normatively to tackling modern slavery.